Iron-manganese metal coordination polymer for separating xenon / krypton mixed gas as well as preparation method and application of iron-manganese metal coordination polymer

By constructing a cage structure of iron-manganese metal coordination polymer material, using high polar bonds and fluorine atoms, the problem of separation between xenon and krypton in the prior art was solved, and efficient and low-energy-consuming xenon and krypton gas were achieved, with a separation coefficient of 10.

CN119613749APending Publication Date: 2025-03-14武夷学院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411766393.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently and with low energy consumption for xenon and krypton gas. Traditional adsorbents have low selectivity for xenon/krypton gas, and deep-cold distillation technology consumes a large energy and is costly.

Method used

Using iron-manganese metal coordination polymer material, a material with a cage structure was constructed through bimetallic tri-core cluster [Fe2Mn(μ3-O)] units, 1,3,5-tris(4-carboxyphenyl)benzene and 3,3',5,5'-tetrafluorobiphenyl-4,4'-dicarboxylic acid ligands, and the separation of xenon and krypton gas was achieved using high polarity C-H and C-O bonds and abundant fluorine atoms.

Benefits of technology

The adsorption and binding affinity of this material for xenon and krypton gas is significantly different, and can effectively regulate the force of gas molecules, achieve high selective separation of xenon and krypton gas, and the separation coefficient can reach 10.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613749A_ABST
    Figure CN119613749A_ABST
Patent Text Reader

Abstract

The invention discloses an iron-manganese metal coordination polymer for separating xenon / krypton mixed gas and a preparation method and application thereof. The iron-manganese metal coordination polymer is sufficient in raw material source, simple in preparation method, good in stability, adjustable and capable of meeting diversified industrial separation requirements. The ferro-manganese metal coordination polymer material has high selectivity, xenon and krypton can be accurately separated, and the selective separation coefficient of xenon / krypton mixed gas (the volume ratio is 20: 80) reaches 10.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coordination chemistry, and in particular relates to an iron-manganese metal coordination polymer for separating a xenon / krypton mixed gas, and a preparation method and application thereof. Background Art

[0002] Xenon and krypton are known as "golden gases" and have high application value in core fields such as optics, semiconductors, satellites and medical equipment. The content of xenon and krypton in the earth's atmosphere is extremely rare, with concentrations of only 0.09 and 1.1 ppm. In industry, the mixture of xenon and krypton is mainly obtained as a by-product of low-temperature distillation of air, and further cryogenic distillation is required to obtain high-purity xenon and krypton. However, cryogenic distillation technology has high energy consumption, high cost, and low output, which is not conducive to development and application. Therefore, it is urgent and important to develop a low-energy and low-cost alternative method for efficient xenon / krypton separation.

[0003] However, since xenon and krypton are inert atomic gases with similar kinetic diameters (xenon: And Krypton: ) and similar physical properties make xenon / krypton separation one of the challenging industrial processes. Physical adsorption separation technology based on porous materials is an effective means to replace traditional energy-intensive separation technology, which is of great significance to the realization of energy conservation and green sustainable development strategic goals. However, since xenon and krypton atoms have no dipole moment or quadrupole moment, they are difficult to be polarized by traditional adsorbents (such as activated carbon and zeolite), resulting in low selectivity of most traditional adsorbents for xenon / krypton. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and to briefly introduce some preferred embodiments.

[0005] As one aspect of the present invention, the present invention provides an iron-manganese metal coordination polymer material, whose chemical formula is [Fe 2 Mn(μ 3 -O)(C 14 H 4 O 4 F 4 )(C 27 H 15 O 6 ) 4 / 3 (H 2 O) 3 ], belongs to the trigonal system, the space group is R3m, and the unit cell parameters are α=90°, β=90°, γ=120°, Z=9; where, C 14 H4 O 4 F 4 represents 3,3′,5,5′-tetrafluorobiphenyl-4,4′-dicarboxylic acid from which two formic acid hydrogen atoms have been removed, C 27 H 15 O 6 It represents 1,3,5-tris(4-carboxyphenyl)benzene from which three formic acid hydrogen atoms have been removed.

[0006] In a second aspect, the present invention provides a method for preparing an iron-manganese metal coordination polymer material, which comprises the following steps:

[0007] Iron salt, manganese salt, 3,3',5,5'-tetrafluorobiphenyl-4,4'-dicarboxylic acid, 1,3,5-tri(4-carboxyphenyl)benzene and acetic acid are mixed, put into a high-pressure reactor containing an organic solvent, and then reacted at a constant temperature of 368-398K to obtain the iron-manganese metal coordination polymer material.

[0008] Furthermore, the molar ratio of the iron salt, the manganese salt, the 3,3′,5,5′-tetrafluorobiphenyl-4,4′-dicarboxylic acid and the 1,3,5-tri(4-carboxyphenyl)benzene is 4:1 to 3:1 to 3:1N4.

[0009] Preferably, the molar ratio of the iron salt, the manganese salt, the 3,3′,5,5′-tetrafluorobiphenyl-4,4′-dicarboxylic acid and the 1,3,5-tri(4-carboxyphenyl)benzene is 4:2:2:3.

[0010] Furthermore, the iron salt is one of ferric chloride hexahydrate or ferric nitrate nonahydrate; the manganese salt is one of manganese nitrate tetrahydrate, manganese chloride tetrahydrate or manganese acetate tetrahydrate.

[0011] Furthermore, the organic solvent is N,N-dimethylformamide solution, and the molar ratio of the iron salt to the organic solvent is 1:600-1000.

[0012] Furthermore, the volume ratio of the acetic acid to N,N-dimethylformamide is 1:10-30.

[0013] Furthermore, the reaction time is 3 days.

[0014] In a third aspect, the present invention provides an application of an iron-manganese metal coordination polymer material, wherein the iron-manganese metal coordination polymer material can be used as a functional material for separating a xenon / krypton gas mixture.

[0015] In the present invention, based on the bimetallic trinuclear cluster [Fe 2 Mn(μ 3-O)] units, using 1,3,5-tri(4-carboxyphenyl)benzene and 3,3',5,5'-tetrafluorobiphenyl-4,4'-dicarboxylic acid ligands, a rare iron-manganese metal coordination polymer material with a cage-in-cage structure was constructed through a framework intercalation strategy. There are highly polar CH and CO bonds and abundant fluorine atoms on the surface of the cage, so the cage-in-cage pore environment shows highly polarized and highly fluorine-friendly characteristics, which makes the iron-manganese metal coordination polymer material have significant differences in adsorption and binding affinity for xenon and krypton, so as to regulate the interaction with different gas molecules to achieve the purpose of separating xenon and krypton.

[0016] Beneficial effects of the invention: The invention provides an iron-manganese metal coordination polymer material, which has sufficient raw material sources, simple preparation methods, good stability, and adjustability, and can meet the diverse industrial separation needs. The iron-manganese metal coordination polymer material has high selectivity and can accurately separate xenon and krypton. The selective separation coefficient of xenon / krypton mixed gas (volume ratio of 20:80) can reach 10. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for describing the embodiment, wherein:

[0018] Figure 1 This is a molecular structure diagram of the iron-manganese metal coordination polymer material obtained in Example 1 of the present invention.

[0019] Figure 2 This is a three-dimensional structural diagram of the iron-manganese metal coordination polymer material obtained in Example 1 of the present invention.

[0020] Figure 3 This is a single-component adsorption curve of xenon and krypton for the iron-manganese metal coordination polymer material obtained in Example 1 of the present invention.

[0021] Figure 4 This is a diagram showing the adsorption separation of a xenon / krypton gas mixture passing through a filling column filled with the iron-manganese metal coordination polymer material obtained in Example 1 of the present invention (in the xenon / krypton gas mixture, the volume ratio of xenon / krypton is 20:80). DETAILED DESCRIPTION

[0022] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0023] The metal-organic framework material [Fe 2 Mn(μ 3 -O)(C 14 H 4 O 4 F4 )(C 27 H 15 O 6 ) 4 / 3 (H 2 O) 3 ] is obtained by solvent thermal method, and the specific reaction formula is:

[0024] 2FeCl 3 +Mn(NO 3 ) 2 +C 14 H 6 F 4 O 4 +4 / 3C 27 H 18 O 6 +4H 2 O→[Fe 2 Mn(μ 3 -O)(C 14 H 4 O 4 F 4 )(C 27 H 15 O 6 ) 4 / 3 (H 2 O) 3 ]+2HNO 3 +6HCl

[0025] Among them, C 14 H 6 F 4 O 4 represents 3,3',5,5'-tetrafluorobiphenyl-4,4'-dicarboxylic acid, C 27 H 18 O 6 represents 1,3,5-tris(4-carboxyphenyl)benzene, C 14 H 4 O 4 F 4 represents 3,3′,5,5′-tetrafluorobiphenyl-4,4′-dicarboxylic acid with two formic acid hydrogen atoms removed, C 27 H 15 O 6 It represents 1,3,5-tris(4-carboxyphenyl)benzene from which three formic acid hydrogen atoms have been removed.

[0026] Embodiment 1:

[0027] The hexahydrated ferric chloride, tetrahydrated manganese nitrate, 3,3',5,5'-tetrafluorobiphenyl-4,4'-dicarboxylic acid and 1,3,5-tri(4-carboxyphenyl)benzene were mixed in a molar ratio of 4:2:2:3 and placed in a solution containing 3 ml of N,N-dimethylacetamide solvent. After being fully mixed, the mixture was transferred to a 20 ml polytetrafluoroethylene-lined autoclave, and 160 microliters of acetic acid solution was added. The amount of the hexahydrated ferric chloride was controlled to be about 14 mg. The mixture was then reacted at a constant temperature of 383 K for 3 days, cooled naturally to room temperature, filtered, washed and dried at room temperature to obtain brown crystals as an iron-manganese metal coordination polymer material [Fe 2 Mn(μ 3 -O)(C 14 H 4 O 4 F 4 )(C 27 H 15 O 6 ) 4 / 3 (H 2 O) 3 ], where C 14 H 4 O 4 F 4 represents 3,3′,5,5′-tetrafluorobiphenyl-4,4′-dicarboxylic acid with two formic acid hydrogen atoms removed, C 27 H 15 O 6 It represents 1,3,5-tris(4-carboxyphenyl)benzene from which three formic acid hydrogen atoms have been removed.

[0028] The brown crystals obtained in Example 1 were tested. The single crystal X-ray diffractometer test showed that the brown crystals were the target compound, i.e., the iron-manganese metal coordination polymer material. X-ray single crystal diffraction data were collected on an Agilent SuperNova single crystal diffractometer. The MoKα molybdenum target (wavelength of 0.71073 angstroms) was used to collect diffraction data in ω scanning mode. All non-hydrogen coordinates were obtained by the direct method and full matrix least squares method using the SHELXL-2014 program. The "crystallographic parameters" of the compound are shown in Table 1, and the molecular structure diagram is shown in Figure 1 , the three-dimensional structure diagram is shown in Figure 2 .

[0029] Table 1 Iron-manganese metal coordination polymers [Fe 2 Mn(μ 3 -O)(C 14 H 4 O 4 F 4 )(C 27 H 15 O 6 ) 4 / 3 (H2 O) 3 Crystallographic parameters and structural analysis of

[0030]

[0031]

[0032] Note: R 1 =∑||F o |-|F c || / ∑|F o |,wR 2 =[∑w(F o 2 -F c 2 ) 2 / ∑w(F o 2 ) 2 ] 0.5 .

[0033] The iron-manganese metal coordination polymer material in the above embodiment is a brown block crystal, the structure of which comprises a μ 3 -O bridges two iron ions and one manganese ion to form a trinuclear cluster [Fe 2 Mn(μ 3 -O)] unit, each trinuclear cluster [Fe 2 Mn(μ 3 -O)] is coordinated with two 3,3′,5,5′-tetrafluorobiphenyl-4,4′-dicarboxylate ligands, four 1,3,5-tri(4-carboxyphenyl)benzene ligands and three water molecules, [Fe 2 Mn(μ 3 -O)(COO) 6 ] units form a three-dimensional framework under the bridging of these two types of ligands.

[0034] As shown in Table 1, the crystal structure parameters of the present invention are: the chemical formula is [Fe 2 Mn(μ 3 -O)(C 14 H 4 O 4 F 4 )(C 27 H 15 O 6 ) 4 / 3 (H 2 O) 3 ],(C 14 H 4 O 4 F 4represents 3,3′,5,5′-tetrafluorobiphenyl-4,4′-dicarboxylic acid from which two formic acid hydrogen atoms have been removed, C 27 H 15 O 6 represents 1,3,5-tris(4-carboxyphenyl)benzene with three formic acid hydrogen atoms removed, belonging to the trigonal system, with a space group of R3m and a unit cell parameter of α = 90°, β = 90°, γ = 120°, and Z = 9. The iron-manganese metal coordination polymer material can effectively separate a xenon / krypton gas mixture.

[0035] Iron-manganese metal coordination polymer material is a double intercalated structure material, which exhibits excellent xenon / krypton separation performance due to its matching cage structure and highly polarized and fluorine-friendly microporous environment. Figure 3 As shown, the adsorption isotherm of xenon is significantly different from that of krypton. Under different pressures, the adsorption capacity of xenon is significantly higher than that of krypton. At 273K and 1 bar, the adsorption of xenon is about 117 cubic centimeters per gram, while the adsorption of krypton is only about 33 cubic centimeters per gram. At low pressure of 0.1 bar, the adsorption of xenon is about 26 cubic centimeters per gram, while the adsorption of krypton is only about 4 cubic centimeters per gram. The adsorption ratio of xenon to krypton is 6 to 7. According to simulation calculations, the separation factor of the xenon / krypton mixture (volume ratio of 20:80) at low pressure is about 10, indicating that the iron-manganese metal coordination polymer material can be used as a material for selective adsorption and separation of xenon / krypton mixtures. Figure 4 As shown, at 298K, when 2 ml / min of a xenon / krypton (volume ratio of 20:80) mixture passes through an adsorption column equipped with an iron-manganese metal coordination polymer material, the krypton gas retains a short time in the adsorption column, penetrates from the adsorption column at about 9 minutes / gram (in units of "penetration time / sample mass"), and quickly reaches saturation to obtain high-purity krypton gas (≥99.9%), while the xenon gas retains a time of more than 40 minutes / gram in the adsorption column, and all of the xenon gas flows out at about 60 minutes / gram. The long penetration time interval between xenon and krypton in the adsorption column indicates that the iron-manganese metal coordination polymer material can achieve effective separation of the xenon / krypton mixture.

[0036] Embodiment 2:

[0037] Ferric nitrate nonahydrate, manganese nitrate tetrahydrate, 3,3',5,5'-tetrafluorobiphenyl-4,4'-dicarboxylic acid and 1,3,5-tri(4-carboxyphenyl)benzene were mixed in a molar ratio of 2:1:1:1 and placed in a solution containing 3 ml of N,N-dimethylacetamide solvent. After being fully mixed, the mixture was transferred to a 20 ml polytetrafluoroethylene-lined autoclave, and 190 microliters of acetic acid solution was added. The amount of ferric nitrate nonahydrate was controlled to be about 20 mg. The mixture was then reacted at a constant temperature of 378 K for 3 days, cooled naturally to room temperature, filtered, washed, and dried at room temperature to obtain brown crystals as an iron-manganese metal coordination polymer material [Fe 2 Mn(μ 3 -O)(C 14 H 4 O 4 F 4 )(C 27 H 15 O 6 ) 4 / 3 (H 2 O) 3 ],(C 14 H 4 O 4 F 4 represents 3,3′,5,5′-tetrafluorobiphenyl-4,4′-dicarboxylic acid from which two formic acid hydrogen atoms have been removed, C 27 H 15 O 6 represents 1,3,5-tris(4-carboxyphenyl)benzene from which three formic acid hydrogen atoms have been removed).

[0038] Embodiment 3:

[0039] The hexahydrated ferric chloride, tetrahydrated manganese acetate, 3,3',5,5'-tetrafluorobiphenyl-4,4'-dicarboxylic acid and 1,3,5-tri(4-carboxyphenyl)benzene were mixed in a molar ratio of 6:3:2:2 and placed in a solution containing 3 ml of N,N-dimethylacetamide solvent. After being fully mixed, they were transferred to a 20 ml polytetrafluoroethylene-lined autoclave, and 250 microliters of acetic acid solution were added. The amount of the hexahydrated ferric chloride was controlled to be about 16 mg. The reaction was then carried out at a constant temperature of 393 K for 3 days, and the reaction was naturally cooled to room temperature, filtered, washed, and dried at room temperature to obtain brown crystals as the iron-manganese metal coordination polymer material [Fe 2 Mn(μ 3 -O)(C 14 H 4 O 4 F 4 )(C 27 H 15 O 6 ) 4 / 3 (H 2 O)3 ],(C 14 H 4 O 4 F 4 represents 3,3′,5,5′-tetrafluorobiphenyl-4,4′-dicarboxylic acid from which two formic acid hydrogen atoms have been removed, C 27 H 15 O 6 represents 1,3,5-tris(4-carboxyphenyl)benzene from which three formic acid hydrogen atoms have been removed).

[0040] Comparative Example 1:

[0041] The hexahydrated ferric chloride, tetrahydrated manganese acetate, 4,4′-biphenyl-dicarboxylic acid and 1,3,5-tri(4-carboxyphenyl)benzene were mixed in a molar ratio of 6:3:2:2 and placed in a solution containing 3 ml of N,N-dimethylacetamide solvent, and after being fully mixed, transferred to a 20 ml polytetrafluoroethylene-lined autoclave, and then 210 microliters of acetic acid solution were added, wherein the amount of hexahydrated ferric chloride was controlled to be about 16 mg, and then the reaction was carried out at a constant temperature of 383K for 3 days, and then naturally cooled to room temperature, filtered, washed, and dried at room temperature to obtain brown crystals as an isostructural non-fluorinated iron-manganese metal coordination polymer material, [Fe 2 Mn(μ 3 -O)(C 14 H 8 O 4 )(C 27 H 15 O 6 ) 4 / 3 (H 2 O) 3 ],(C 14 H 8 O 4 represents 4,4′-biphenyl-dicarboxylic acid with two formic acid hydrogen atoms removed, C 27 H 15 O 6 represents 1,3,5-tris(4-carboxyphenyl)benzene with three formic acid hydrogen atoms removed, belonging to the trigonal system, with a space group of R3m and a unit cell parameter of α=90°, β=90°, γ=120°, Z=9.

[0042] Through experimental research, the xenon adsorption capacity of fluorinated iron-manganese metal coordination polymers is significantly higher than that of non-fluorinated iron-manganese metal coordination polymer materials. For example, at 273K and 1 bar, the xenon adsorption capacity of the fluorinated iron-manganese metal coordination polymer of Example 1 (about 117 cubic centimeters / gram) is 1.3 times that of the non-fluorinated iron-manganese metal coordination polymer material of Example 1 (about 90 cubic centimeters / gram), while the adsorption capacity of krypton is almost the same. It shows that the introduction of fluorine functional groups forms a highly fluorine-friendly microporous environment, promotes the close contact between xenon and the pore surface, and provides the best pore environment for the capture of xenon. At the same time, by comparing the separation coefficients of the xenon / krypton mixed gas (volume ratio of 20:80) under low pressure between the two, the xenon / krypton selective separation coefficient (about 10) of the fluorinated iron-manganese metal coordination polymer of Example 1 is about 1.6 times that of the non-fluorinated iron-manganese metal coordination polymer material (about 6). The obvious difference in the separation coefficients of the two further illustrates the importance of fluorine substituents in specific structures.

[0043] Comparative Example 2:

[0044] Copper nitrate, 1,3,5-tris(3,5-difluoro-4-carboxyphenyl)benzene and 4,4′-bipyridine were mixed in a molar ratio of 4:1:1 and placed in a 20 ml polytetrafluoroethylene-lined autoclave containing 1.5 ml N,N-dimethylformamide and 1.5 ml 4,4′-bipyridine solvent, and then 0.12 ml trifluoroacetic acid solution was added, wherein the amount of copper nitrate was controlled to be about 7 mg, and then the reaction was carried out at a constant temperature of 353-373K for 36 hours to obtain a blue polygonal crystal as a copper metal coordination polymer material [Cu 2 (C 27 F 6 H 9 O 6 ) 4 / 3 (C 10 H 8 N 2 )],(C 27 F 6 H 9 O 6 represents 1,3,5-tris(3,5-difluoro-4-carboxyphenyl)benzene, C 10 H 8 N 2 represents 4,4′-bipyridine), belongs to the cubic system, the space group is Pm3n, and the unit cell parameter is α=90°, β=90°, γ=90°, Z=6.

[0045] Experimental studies have shown that the xenon adsorption capacity of the copper metal coordination polymer material at 273K and 1 bar is only about 23 cubic centimeters per gram, which is much smaller than the xenon adsorption capacity of the iron-manganese metal coordination polymer. This shows that only in a specific structure, the pore environment modified by the fluorine group can promote the separation of xenon and krypton.

[0046] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. An iron-manganese metal coordination polymer for separating a xenon / krypton gas mixture, characterized in that: The chemical formula of the iron-manganese metal coordination polymer is: [Fe2Mn(μ3-O)(C 14 H4O4F4)(C 27 H 15 O6) 4 / 3 (H2O)3], belongs to the trigonal system, the space group is R3m, and the unit cell parameters are α=90°, β=90°, γ=120°, Z=9.

2. A method for preparing an iron-manganese metal coordination polymer for separating a xenon / krypton gas mixture, characterized in that: Iron salt, manganese salt, 3,3',5,5'-tetrafluorobiphenyl-4,4'-dicarboxylic acid, 1,3,5-tri(4-carboxyphenyl)benzene and acetic acid are mixed, put into a reaction kettle containing an organic solvent, and reacted at a constant temperature of 358-393K to obtain an iron-manganese metal coordination polymer.

3. The method for preparing the iron-manganese metal coordination polymer for separating xenon / krypton mixed gas according to claim 2, characterized in that: The molar ratio of the iron salt, the manganese salt, the 3,3',5,5'-tetrafluorobiphenyl-4,4'-dicarboxylic acid and the 1,3,5-tri(4-carboxyphenyl)benzene is 4:1-3:1-3:1-4.

4. The method for preparing the iron-manganese metal coordination polymer for separating xenon / krypton mixed gas according to claim 2, characterized in that: The molar ratio of the iron salt, the manganese salt, the 3,3′,5,5′-tetrafluorobiphenyl-4,4′-dicarboxylic acid and the 1,3,5-tri(4-carboxyphenyl)benzene is 4:2:2:

3.

5. The method for preparing an iron-manganese metal coordination polymer for separating a xenon / krypton mixed gas according to any one of claims 2 to 4, characterized in that: The iron salt is ferric chloride hexahydrate or ferric nitrate nonahydrate; the manganese salt is one of manganese nitrate tetrahydrate, manganese chloride tetrahydrate or manganese acetate tetrahydrate.

6. The method for preparing an iron-manganese metal coordination polymer material for separating a xenon / krypton mixed gas according to any one of claims 2 to 4, characterized in that: The organic solvent is N,N-dimethylformamide, and the molar ratio of the iron salt to the organic solvent is 1:600-1000.

7. The method for preparing the iron-manganese metal coordination polymer material for separating xenon / krypton mixed gas according to claim 6, characterized in that: The volume ratio of the acetic acid to the N,N-dimethylformamide is 1:10-30.

8. The method for preparing an iron-manganese metal coordination polymer material for separating a xenon / krypton mixed gas according to any one of claims 2 to 4, characterized in that: The reaction time is 3 days.

9. Use of the iron-manganese metal coordination polymer material for separating a xenon / krypton mixed gas according to claim 1 as a functional material for separating a xenon / krypton mixed gas.